PENERAPAN METODE PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 11 KADUR KECAMATAN RUPAT UTARA - Rosalita, Rosalita; Kurniaman, Otang; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research was done because low of IPS study result of the fourth grade students at SDN 11 Kadur. KKM stated at school was 70. From 20 students, only 10 students that reached KKM, whereas student did not still reach KKM yet were 10 students. With score mean of class was 63,50. For solving the problem, there for the researcher implement problem solving method. The goal of research was for increasing IPS study result of the fourth grade at SDN 11 Kadur by implementing problem solving method. The research was classroom action research. The technique of collecting data by using observation and test. The result of research was collected at first meeting of cycles, the teacher’s activity on classification “enough” (58,33%), after at second meeting, that known the teacher’s activity on classification “good”(66.67%). at first meeting of cycles II, teacher’s activity on classification ”good”(70,83%), after at second meeting teacher’s activity on classification “very good”(95,83%). At first meeting cycle I, students’ activity on classification “poor”(50,00%), at second meeting students’ activity on classification ”good” (62,50%). At first meeting of cycles II, the students’ activity on classification “good”(75,00%). At second meeting students’ activity on classification “very good”(87,33%).At cycles 1 known that total of students reached KKM were 16 students (80,00%) with mean score 73,50, At cycles II, total of students reached KKM were 19 students (95.00%) with mean score 80,75. Based on this research can be concluded that by implementing problem solving method can increase IPS study result of the fourth grade students at SDN 11 Kadur sub-district Rupat Utara.Keywords: Problem solving method, social studies students achievement